Analisis Evaluasi Sistem Keamanan Pada Museum Bank Indonesia - Syaffa Prameyswari; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Pusat Riset dan Inovasi Nasional, 2024)
The main problem discussed is the Evaluation Analysis of the Security System at the Bank Indonesia Museum based on the standards set by the International Council of Museums (ICOM) and the Indonesian Museum Handbook. This research uses a descriptive evaluative method with a qualitative approach, namely analyzing and assessing museum security. Data collection techniques are carried out by means of observation, interviews, documentation, and reviewing literature studies. The theory used is the museum security system and evaluation of the implementation of museum security. Based on the results of the research that has been carried out, it has been found that there are advantages and disadvantages in the security system of the Bank Indonesia Museum, including the advantage that the Bank Indonesia Museum has minimal threat of theft because there are guards in each collection, and most of the security systems meet standards. security supporting infrastructure, namely that there are still deficiencies in human resources and in terms of technology that can threaten building security.